The Impact of Payment Gateway Adoption, Digital Financial Literacy, and Financial Inclusion on MSMEs' Financial Performance - Lamidi Lamidi; Marjam Desma Rahadhini; Sisca Dian Rahmawati; Nabilla Putri Amaria; Mahmud Mahmud; Tubagus Achmad Darodjat (Jurnal Telekomunikasi dan Informatika, 2025)
The pandemic has significantly impacted Micro, Small, and Medium Enterprises (MSMEs), especially in Solo Raya, where adaptation to digital technology is now crucial for survival in an increasingly complex market. This research focuses on the influence of three key factors—Fintech-based payment gateways, digital financial literacy, and financial inclusion—on the financial performance of MSMEs in Solo Raya. The adoption of Fintech is vital due to the rise of cashless transactions and shifting consumer behaviors, making digital financial management essential for MSMEs to thrive. Solo Raya, known for its rich cultural and culinary heritage, has a growing MSME sector that drives the local economy. However, the lack of digital financial literacy and financial inclusion poses challenges for business growth and financial stability. This study employs a quantitative method, using a survey distributed to culinary MSMEs across Solo Raya, including Surakarta, Wonogiri, Klaten, Boyolali, and Karanganyar. Data is analyzed with SEM-PLS (Partial Least Square), assessing validity, reliability, and the relationships between variables through SmartPLS. This research aims to provide insights that will help MSMEs effectively adapt to digital advancements, ensuring sustainable growth and competitiveness. The results which states that digital payment adoptions, digital financial literacy, financial inclusion has impact on the MSME’s financial performance.